Answer:
¼(√6 + √2)
Explanation:
We want to find cos (π/12) in surd form.
Now, cos (π/12) can be expressed as;
cos [(π/4) - (π/6)]
Now, from trig derivations we know that;
Cos (A - B) = CosACosB + sinAsinB
Thus;
cos [(π/4) - (π/6)] = cos(π/4)Cos(π/6) + sin(π/4)sin(π/6)
Now, in surd form;
cos(π/4) = sin(π/4) = (√2)/2
Cos(π/6) = (√3)/2
sin(π/6) = 1/2
Thus, Plugging in relevant values to get;
cos(π/4)Cos(π/6) + sin(π/4)sin(π/6) = ((√2)/2 × (√3)/2) + ((√2)/2 × 1/2)
This gives;
((√6)/4) + ((√2)/4) = ¼(√6 + √2)